Learning preferences among ethnically diverse nursing students exposed to a variety of collaborative learning approaches including problem-based learning. - Ishida DN (Learning Preferences Among Ethnically Diverse Nursing Students Exposed to a Variety of Collaborative Learning Approaches Including Problem-based Learning, 1995)
Collaborative peer learning approaches facilitate student learning. Problem-based learning (PBL), an inquiry form of collaborative learning (CL), has been utilized in the medical education. Its use in nursing education is relatively new and not well documented. PBL and other CL approaches were utilized in a nursing department's curriculum. Answers to the following hypotheses were sought: (1) Nursing students will find PBL facilitates their educational process, and, (2) Students from various ethnic groups respond differently to PBL. The CL approaches have their theoretical grounding in Vygotsky's theory on the social origins of learning. A life history questionnaire administered in the second semester of the program was utilized to provide the socio-cultural context of learning for the 17 student informants in a nursing class. Twelve of the 17 were interviewed before graduation. Participant-observation was utilized throughout the study. While Hypothesis I was supported, Hypothesis II was not. Student informants from various Asian-Pacific and Caucasian backgrounds responded positively to CL, PBL in particular. A majority of students processed new information by interacting with others. Relationships with peers and faculty were enhanced by the collaborative groups. Students reported taking ownership for their learning, learning team skills, and gaining increased confidence. Clarification of student and faculty role and ground rules were needed since the experience was generally new. Regularly evaluating the group's ability to work together was also important.